Analysis of fractal radiation patterns from concentric-ring hexagonal arrays - Boualleg, A.; Merabtine, N.; Benslama, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
These hexagonal arrays are becoming increasingly popular, especially for their applications in the area of wireless communications. The overall objective of this article has been to use the theoretical foundation developed for the analysis of radiation patterns and design of the hexagonal arrays. A technique has been developed for the analysis of radiation patterns from concentric ring arrays. A family of functions, known as generalized Weierstrass functions, has been shown to play a key role in the theory of fractal radiation pattern analysis.